Patients with systemic lupus erythematosus, myositis, rheumatoid arthritis and scleroderma share activation of a common type I interferon pathway - Higgs, Brandon W; Liu, Zheng; White, Barbara; Zhu, Wei; White, Wendy I; Morehouse, Chris; Brohawn, Philip; Kiener, Peter A; Richman, Laura; Fiorentino, David; Greenberg, Steven A; Jallal, Bahija; et al. (Annals of the rheumatic diseases, 2011)
Objective To characterise activation of the type I interferon (IFN) pathway in patients with systemic lupus erythematosus (SLE), dermatomyositis (DM), polymyositis (PM), rheumatoid arthritis (RA) and systemic scleroderma (SSc) and to evaluate the potential to develop a molecular diagnostic tool from the peripheral blood that reflects this activation in disease-affected tissues. Methods Overexpressed transcripts were identified in the whole blood (WB) of 262 patients with SLE, 44 with DM, 33 with PM, 28 with SSc and 89 with RA and compared with 24 healthy subjects using Affymetrix microarrays. A five gene type I IFN signature was assessed in these subjects to identify subpopulations showing both activation and concordance of the type I IFN pathway in the peripheral blood and disease-affected tissues of each disease and to correlate activation of this pathway in the WB with clinical measurements. Results A common set of 36 type I IFN inducible transcripts were identified among the most overexpressed in the WB of all subjects. Significant activation of the type I IFN pathway in subgroups of each of the five diseases studied was observed. Baseline disease activity measurements correlated with a type I IFN gene signature in the WB of subjects with SLE, PM and SSc, as did various serum autoantibody levels in subjects with SLE and DM. This signature was also well correlated between disease-affected tissue and WB in subjects with SLE, DM, PM and SSc. Conclusions The results indicate that the type I IFN pathway is activated in patient subsets of five rheumatic diseases and suggest that these subsets may benefit from anti-IFN therapy.